Adsorption of N and P in Piggery Wastewater by CaCl2 Impregnated Activated Carbons Produced from Coconut Pith - Thi Hoang Oanh, Le; Thi Hien, Nguyen; Thi Ha, Nguyen; Hong, Tran Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 42 No 2DO - 10.25073/2588-1094/vnuees.5440, 2026)
Sample Piggery wastewater contains high content of N and P, which are the primary cause of surface water eutrophication. Removal of N and P is less superior than recovery of them as important nutrients for crops. This study assessed activated carbons (ACs) produced from coconut pitch in adsorption of N and P from piggery wastewater toward utilization as fertilizer. The ACs were produced by impregnation method using CaCl 2 1M (pre-impregnated, and post impregnated products were compared with not-impregnated product). The saturated adsorption time was strongly dependent on target ions (PO 4 3- , NO 3 - , and NH 4 + ) and type of modification methods. This time was shortest for NO 3 - and longest for NH 4 + . Optimal pH for adsorption were 9, 4 and 6-7 for PO 4 3- , NO 3 - , and NH 4 + , respectively and was slightly affected by modification method. Corresponding maximum adsorption capacity was higher for NH 4 + than for PO 4 3- and NO 3 - ; However no improvement effect was observed for modified ACs by CaCl 2 impregnation. Application of CaCl 2 impregnation method in AC production for N and P recovery from piggery wastewater needs further investigation.